Seed bank in relation to successional gradient on the glacier foreland of Skaftafellsjökull glacier - Wahl, Veronika (2011)
Crucial for understanding primary vegetation succession are the formation and dynamics of soil seed banks over time. Better knowledge of soil seed banks in reference to the aboveground vegetation and surrounding landscape will lead to solving the question on the driving forces of primary succession and the importance of seed dispersal and seed dormancy in the soil. Our study estimated the soil seed bank and discussed the findings with respect to the aboveground vegetation along a chronosequence on the glacier foreland of Skaftafellsjökull in South-East Iceland. Soil samples were randomly taken within three successional stages deglaciated at different times (ca. 2002, 1945 and 1890; here the first two are discussed further). The seed were extracted using a floatation method, classified morphologically and linked to their appropriate plant taxa by using germinated seeds. It was found that (1) with ongoing succession the seed diversity and size of the seed bank increases considerably. (2) Differences in seed bank size and diversity within a successional stage could not be explained by the surrounding flora and landscape. (3) In general the soil seed bank neither reflected the present aboveground vegetation nor earlier or later successional stages.